Komunikasi Publik Dalam Pengawasan Peraturan Walikota Lubuk Linggau Nomor 38 Tahun 2021: Analisis Perspektif Masyarakat terhadap Implementasi Penerimaan Peserta Didik Baru - Ade Putra, Rizki; Alimansyah (STAI Bumi Silampari, 2025)
This study analyzes public communication in the supervision of the Mayor of Lubuk LinggauRegulation No. 38 of 2021 concerning the Admission of New Students (PPDB) at the kindergarten, elementary, and junior high school levels, from the perspective of the community as policy beneficiaries. Effective public communication is a key factor in the success of educational policy oversight; however, its implementation in Lubuk Linggau City still faces various challenges. This quantitative descriptive research employs Dunn’s (2003) policy evaluation framework, which includes five dimensions: effectiveness, efficiency, adequacy, equity, and responsiveness. Data were collected through a survey of 39 respondents who participated in DPRD supervisory activities, selected purposively from a total of 100 participants. The results indicate that public communication in PPDB supervision falls under the “fairly implemented” category, with a grand mean score of 2.021. The efficiency dimension received the highest score (mean 1.692), while the responsiveness dimension received the lowest (mean 2.205), indicating weak two-way communication mechanisms between policymakers and the public. These findings highlight the importance of strengthening public communication strategies in the supervision of education policies to enhance transparency, accountability, and community participation in local education governance.